2008
DOI: 10.4161/cbt.7.8.6262
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of p38-stress kinase sensitizes quiescent leukemic cells to anti-mitotic drugs by inducing proliferative responses in them

Abstract: Quiescent cells pose a formidable challenge in clinical management of leukemia, since they escape chemo-radiotherapy and become a source of post-therapy relapse. These cells may be refractory to various known growth-promoting signals, making it imperative to identify the biochemical signals necessary to coax them into mitosis. Using serum-starved cell lines as an experimental model of quiescent leukemic cells (QLCs), we demonstrate that a suppression of p38 stress kinase by pharmacological means forms a suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Cells were starved in low serum (0.5% FBS) medium overnight to prepare Quiescent Leukemic Cells (QLCs) from them. [36] QLCs were subjected to various treatments as follows:…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Cells were starved in low serum (0.5% FBS) medium overnight to prepare Quiescent Leukemic Cells (QLCs) from them. [36] QLCs were subjected to various treatments as follows:…”
Section: Cell Culturementioning
confidence: 99%
“…The data represent mean ± S.E.M of three independent experiments (** P ≤ 0.01) to treatment, and their presence is associated with relapses. [13,15,16] In 2008, Vaidya et al [36] showed that inhibition of p38 mitogen-associated protein kinase (MAPK) sensitizes the QLCs to antimitotic agents 5-FU and cytosine arabinoside (Ara-C). Since the treatment of QLCs with low concentrations of curcumin was pushing the cells into proliferation, we conjectured that this proliferative response could be translated to increase the sensitivity of the leukemic cells to antimitotic agents.…”
Section: -Fluorouracil Inhibits the Proliferation Of Qlcs In A Dose-mentioning
confidence: 99%
See 2 more Smart Citations
“…In the study reported in this issue of Cancer Biology & Therapy by Vauidya et al 19 suppression of p38 by pharmacological inhibitors rescued growth-arrested cells to sensitivity to cytotoxic agents which are inactive on quiescent cells. This is an important example of how a modulator of cell signalling can be successfully used to enhance the effects of traditional cytotoxic chemotherapy.…”
mentioning
confidence: 95%